Aptamers in hematological malignancies and their potential therapeutic implications. (October 2016) - Ouyang, Wanyan; Yu, Ziqiang; Zhao, Xiaohong; Lu, Shiyun; Wang, Zhi
Highlights: Aptamers have shown advantages outweighed antibody. Their therapeutic or diagnostic potential is of increasing research priority. Aptamers may directly inhibit the function of target proteins, be engineered for delivery agents, or to identify novel targets. Aptamer-based therapies in hematologic malignancies is also rapidly expanding with promising results from in-vivo or in-vitro studies. Aptamer-based products have not yet successfully entered clinical use. Much effort need to enhance aptamer safety and commercialization. Abstract: Aptamers are short DNA/RNA oligonucleotides selected by the process called Systematic Evolution of Ligands by Exponential Enrichment (SELEX). Due to their functional similarity to monoclonal antibodies with some superior characters, such as high specificity and affinity, flexible modification and stability, and lack of toxicity and immunogenicity, they are promising alternative and complementary targeted therapy for hematologic malignancies. The trends in aptamer technology including production, selection, modifications are briefly discussed in this review. The key aspect is to illustrate aptamers against cancer cells in hematologic malignancies especially those that have entered clinical trials. We also discuss some challenges remain in the application of aptamers.